2014
DOI: 10.1016/j.ejphar.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of dipyrone in peripheral tissue involves two different mechanisms: Neuronal KATP channel opening and CB1 receptor activation

Abstract: Dipyrone (metamizole) is an analgesic pro-drug used to control moderate pain. It is metabolized in two major bioactive metabolites: 4-methylaminoantipyrine (4-MAA) and 4-aminoantipyrine (4-AA). The aim of this study was to investigate the participation of peripheral CB1 and CB2 cannabinoid receptors activation in the anti-hyperalgesic effect of dipyrone, 4-MAA or 4-AA. PGE2 (100ng/50µL/paw) was locally administered in the hindpaw of male Wistar rats, and the mechanical nociceptive threshold was quantified by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
5
40
0
6
Order By: Relevance
“…The spasmolytic effect of dipyrone might be explained through stimulation of the cannabis receptors . There is probably also a peripheral antinociceptive effect due to activation of ATP‐sensitive K‐channels . The antipyretic effect is achieved by COX‐2 inhibition …”
Section: Introductionmentioning
confidence: 99%
“…The spasmolytic effect of dipyrone might be explained through stimulation of the cannabis receptors . There is probably also a peripheral antinociceptive effect due to activation of ATP‐sensitive K‐channels . The antipyretic effect is achieved by COX‐2 inhibition …”
Section: Introductionmentioning
confidence: 99%
“…demonstrated greater sensitivity at a 50°C than 55°C hotplate. Nevertheless, dos Santos et al . showed that, similar to dipyrone, the metabolites 4‐MAA and 4‐AA reduce PGE 2 ‐induced hyperalgesia in a nociceptive paw electronic pressure meter test.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the metamizole metabolites mentioned above, which have been known for decades, 2 further metabolites have been identified more recently by liquid chromatography–mass spectrometry–based analyses after oral administration of metamizole to mice: arachidonoyl‐4‐MAA and arachidonoyl‐4‐AA, representing the arachidonoyl amides of 4‐MAA and 4‐AA, respectively . Furthermore, a total of 6 metabolites of metamizole could be detected in the urine of healthy volunteers after oral administration of metamizole.…”
Section: Hepatic Metabolism Of Metamizolementioning
confidence: 99%